METHODS OF EXAMINATION OF PATIENTS SUFFERING FROM EPISPADIAS AND URINARY INCONTINENCE - Khairulla Kh. Khudaynazarov; Fayzullaev T.S (Scholar Express Journals, 2024)
According to WHO, the number of children with congenital pathologies increases every year. If in 1984, 11.2% of newborns had such cases, then in 2004 this figure increased by 12.8%. Of course, there are objective and subjective reasons for this. The objective reasons include the development of medicine over the past 20 years, improved diagnostics, the creation of computed tomography, and timely high-quality ultrasound diagnostics. Subjective reasons include environmental problems, the widespread introduction of industrial chemistry into our lives, urbanization processes, the emergence of ozone holes in the atmosphere, and stress.
Keywords: Epispadias; urinary incontinence; examination methods